Costing a population health management approach for participant recruitment to a diabetes prevention study. Issue 10 (8th May 2021) - Michaud, Tzeyu L; Wilson, Kathryn; Silva, Fabiana; Almeida, Fabio; Katula, Jeff; Estabrooks, Paul
Abstract: Limited research has reported the economic feasibility—from both a research and practice perspective—of efforts to recruit and enroll an intended audience in evidence-based approaches for disease prevention. We aimed to retrospectively assess and estimate the costs of a population health management (PHM) approach to identify, engage, and enroll patients in a Type 1 Hybrid Effectiveness-Implementation (HEI), diabetes-prevention trial. We used activity-based costing to estimate the recruitment costs of a PHM approach integrated within an HEI trial. We took the perspective of a healthcare system that may adopt, and possibly sustain, the strategy in the typical practice. We also estimated replication costs based on how the strategy could be applied in healthcare systems interested in referring patients to a local diabetes prevention program from a payer perspective. The total recruitment and enrollment costs were 360, 424 to accrue 599 participants over approximately 15 months. The average cost per screened and enrolled participant was 263 and 620, respectively. Translating to the typical settings, total recruitment costs for replication were estimated as 193, 971 (range: 43, 827–210, 721). Sensitivity and scenario analysis results indicated replication costs would be approximately 283–444 per patient enrolled if glucose testing was necessary, based on the Medicare-covered services. From a private payer perspective, and without glucose testing, per-participant assessed costs were estimated at 31. A PHM approach can be used to accrue a large number of participants in a short period of time for an HEI trial, at a comparable cost per participant.